Preventive practices and parental attitudes towards snakebites in children in snakebite hotspots of rural Sri Lanka - Indika Gawarammana; Kavinda Dayasiri; Shaluka Jayamanne; Gihan Gunarathna (BMJ Paediatrics Open)
Background Snakebites remain a major public health issue in rural Sri Lanka, particularly among children under 5. Parental attitudes, knowledge and preventive practices significantly influence the risk of snakebites and the effectiveness of first aid responses. This study aimed to assess parental attitudes, knowledge sources and preventive practices related to snakebite prevention and management in children living in snakebite-endemic rural regions of Sri Lanka.Methods A descriptive cross-sectional study was conducted in the Ampara and Polonnaruwa Districts, two snakebite-endemic regions in Sri Lanka. The study targeted parents with at least one child under 5 years old, who were selected through cluster sampling facilitated by Public Health Midwives. A structured, self-administered questionnaire was used to collect data on demographic characteristics, parental attitudes towards snakes and snakebites, knowledge sources and preventive practices.Results A total of 518 parents participated, with the majority being mothers (94.2%). Extreme fear of snakes was reported by 92.7% of participants. Parental beliefs varied, with 23.7% believing that a snake should always be killed after biting a person and 18.0% holding the belief that snakes take revenge. Significant associations were found between extreme fear of snakes and the absence of prior training in snakebite first aid (p=0.035) as well as being a mother (p=0.001). Major challenges in snakebite care included transportation difficulties (90.5%), lack of proximity to hospitals with emergency treatment (81.5%) and reliance on traditional healing practices (32.6%). Traditional healing practices (32.6%) were significantly associated with low socioeconomic status (p=0.001) and low parental education (p=0.001). Social media (42.1%) was the most common source of knowledge on snakebite care. Storing paddy at home was significantly associated with a family history of snakebites (p=0.004)Conclusions Parental fear, cultural beliefs and limited access to training programmes significantly influence snakebite prevention and management practices. Enhancing community-based education, improving healthcare accessibility and incorporating snakebite first-aid training into public health programmes could mitigate the risks and improve outcomes for paediatric snakebite cases in rural Sri Lanka.